A hybrid method for user location anonymisation based on road mobility model. (1st January 2014) - Miura, Kenta; Sato, Fumiaki
Highly accurate positioning devices provide various types of location-based services (LBS). Since location information may reveal private information, preserving location privacy has become a significant issue in LBS. Many different techniques for securing location privacy have been proposed, for example, the concepts of silent period, dummy node, and cloaking region. However, much of this research has not solved the problem that the quality of service (QoS) of LBS decreases when anonymity is improved, and anonymity falls when QoS is improved. In this paper, we present a node density-based location anonymisation scheme that can provide location privacy by a hybrid method using the dummy node and the cloaking region. Especially, we propose a method to keep the anonymity without reducing the QoS of the LBS by setting the cloaking region based on the road mobility model. Simulations are conducted to evaluate our proposed method from the viewpoint of location error in LBS and the probability of tracking a target node. Simulation results show that the probability of tracking a target node by an adversary is reduced and the QoS of LBS is improved.